THE EFFECT OF A MULTIMEDIA- BASED EDUCATIONAL PROGRAM ON THE DEVELOPMENT OF CREATIVE THINKING SKILLS AMONG 8TH GRADE STUDENTS IN COMPUTER SCIENCE IN JORDAN - Abu Mathana, Basma Hassan (Journal of Educational and Psychological Sciences, 2018)
This study aimed at exploring the effect of a multimedia- based educational program on the development of creative thinking among the eighth grade students in computer science in Jordan. In this study, the researcher followed the semi- experimental approach. The study used the Torrance test of creative thinking (verbal image a) with its dimensions (fluency, flexibility, originality) and was applied to a sample of (54) students chosen randomly. The sample consisted of two classes of eighth grade students from Fatima Al Zahra Elementary School for Girls. The experimental group which consisted of (28) students studied the proposed educational program, and the control group which consisted of (26) students studied in the usual way. and then the data were collected and analyzed statistically. The results of the study revealed that there were significant differences at the level of (α = 0.05) in the level of development of creative thinking skills. The experimental group average was (29.30) compared to (17.60) for the control group. The experimental group averages were (13.59، 13.67، 2.04) in sequence for the dimensions (fluency, flexibility, originality) , whereas the control group averages were(7.68، 8.48، 1.44) in sequence for the dimensions (fluency, flexibility, originality). The differences were in favor of the experimental groups This is attributed to the multimedia- based educational program for the eighth grade class in the computer science subject. In the light of the results, some suggestions and recommendations for the use of multi-media in teaching and developing the thinking skills are presented.
Keywords: multimedia; creative thinking; computer topic; eighth grade